Geomagnetic and Ionospheric Responses to the Interplanetary Shock Wave of March 17 2015 - Bravo-Gonzalez, M; Romanova, N (Pleiades Publishing, 2018)
The propagation of perturbation caused by the interplanetary shock wave of March 17, 2015 from the solar wind through the magnetosheath, magnetosphere, and ionosphere down to the Earth’s surface is analyzed. The onboard satellite measurements, global magnetometer network data, and records by the receivers of the global positioning system (GPS) providing the information about the total electron content (TEC) of the ionosphere are used for the analysis. By the example of this event, various aspects of the influence of the interplanetary shock wave on the near-Earth environment and ground-based engineering systems are considered. It is shown which effects of this influence are well described by the existing theoretical models and which ones need additional research. The formation of the fine structure of the magnetic impulse of the storm sudden commencement (SC)—the preliminary impulse (PI) and main impulse (MI)—is considered. The MI and compression of the magnetospheric magnetic field is observed by the GOES and RBSP satellites and on the geomagnetically conjugate stations; however, the PI was only noted on the Earth. The PI was detected in the afternoon sector practically simultaneously (within 1 min) with the shock wave impact on the magnetopause. The wave’s response to the SC includes the strongly decaying resonant oscillations of the magnetic shells and the magnetoacoustic cavity mode. This study supports the possibility of detecting the ionospheric response to the SC by the GPS method. The TEC response to the MI was detected in the auroral latitudes although not on every radio path. The TEC modulation can be associated with the precipitation of superthermal electrons into the lower ionosphere which is undetectable by riometers. The burst in the intensity of the geomagnetically induced currents caused by an interplanetary shock wave turns out to be higher than the currents during the storm’s commencement, although the SC’s amplitude is noticeably lower than the amplitude of the magnetic bay related to the substorm. © 2018, Pleiades Publishing, Ltd.